Respuesta :
Answer:
y = 24x³ - 1
Explanation:
We have:
x = [tex] \frac{1}{2} t[/tex]
This means that:
t = 2x ...............> I
We are also given that:
y = 3t³ - 1 .............> II
Substitute with I in II to eliminate the t as follows:
y = 3t³ - 1
y = 3*(2x)³ - 1
y = 3*8x³ - 1
y = 24x³ - 1
Hope this helps :)
y = 24x³ - 1
Explanation:
We have:
x = [tex] \frac{1}{2} t[/tex]
This means that:
t = 2x ...............> I
We are also given that:
y = 3t³ - 1 .............> II
Substitute with I in II to eliminate the t as follows:
y = 3t³ - 1
y = 3*(2x)³ - 1
y = 3*8x³ - 1
y = 24x³ - 1
Hope this helps :)
x = one divided by two t
x = 1/2t; t = 2x
Substitute the t in the equation:
y = 3t^3 - 1
y = 3(2x)^3 - 1
y = 3(8x^3) - 1
y = 24x^3 - 1
The answer is y = 24x^3 - 1
Hope this helps! Goodluck
x = 1/2t; t = 2x
Substitute the t in the equation:
y = 3t^3 - 1
y = 3(2x)^3 - 1
y = 3(8x^3) - 1
y = 24x^3 - 1
The answer is y = 24x^3 - 1
Hope this helps! Goodluck